Pengaruh Struktur Kepemilikan, Kualitas Audit dan Free Cash Flow terhadap Manajemen Laba: Studi Empiris pada Perusahaan Pertambangan Terdaftar di BEI Tahun 2016-2020 - Putri, Shintya Arifin; NR, Erinos (Jurnal Nuansa Karya Akuntansi, 2023)
This study aims to examine the effect of ownership structure, audit quality and free cash flow on earnings management in mining companies listed on the Indonesia Stock Exchange (IDX). Sample was determined using the purposive sampling method. Sample selection produced 20 companies. The data used is secondary data from the company's annual report. The statistical method used is logistic regression analysis. The of statistical analysis show that institutional ownership and audit quality has a impact on profit management. Ownership and free cash flow do not have a significant impact on revenue management.